2022
DOI: 10.1155/2022/6886752
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine and Promethazine (C+P) Reduce Brain Injury after Ischemic Stroke through the PKC-δ/NOX/MnSOD Pathway

Abstract: Cerebral ischemia-reperfusion (I/R) incites neurologic damage through a myriad of complex pathophysiological mechanisms, most notably, inflammation and oxidative stress. In I/R injury, nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) produces reactive oxygen species (ROS), which promote inflammatory and apoptotic pathways, augmenting ROS production and promoting cell death. Inhibiting ischemia-induced oxidative stress would be beneficial for reducing neuroinflammation and promoting neuronal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Our findings support the hypothesis that suppressing the NLRP3 inflammasome can mitigate brain damage by modulating the inflammatory response [ 25 ]. In addition, we have demonstrated that C + P therapy diminishes ROS levels post-ischemia, contributing to a reduction in oxidative stress and cellular damage [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our findings support the hypothesis that suppressing the NLRP3 inflammasome can mitigate brain damage by modulating the inflammatory response [ 25 ]. In addition, we have demonstrated that C + P therapy diminishes ROS levels post-ischemia, contributing to a reduction in oxidative stress and cellular damage [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We incubated the cells at 5 % CO 2 and 37 °C in a humidified incubator. As previously described [ 29 ], we first prepared an anaerobic chamber by flushing it with a 95 % N 2 and 5 % CO 2 (v/v) mixture, maintaining the temperature at 37 °C. The cell culture medium was then replaced with deoxygenated, glucose-free DMEM to initiate a 2-h OGD phase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is little exacerbation of preexisting epileptic foci by enflurane, the only exception being the case of certain myoclonic-type epilepsies, such as progressive myoclonic epilepsy and photosensitive epilepsy (76). Promethazine reduces brain injury after ischemic stroke through PKC-δ/NOX/MnSOD and RIP1-RIP3 regulated activation of the NLRP3 inflammasome following ischemic stroke (77,78). Miconazole exerts disease-modifying effects in epilepsy by suppressing neuroinflammation via the NF-κB pathway and iNOS production (79).…”
Section: Discussionmentioning
confidence: 99%